Report on stage III Pig-a mutation assays using N-ethyl-N-nitrosourea - comparison with other in vivo genotoxicity endpoints - Cammerer, Zoryana; Bhalli, Javed A.; Cao, Xuefei; Coffing, Stephanie L.; Dickinson, Donna; Dobo, Krista L.; Dobrovolsky, Vasily N.; Engel, Maria; Fiedler, Ronald D.; Gunther, William C.; Heflich, Robert H.; Pearce, Mason G.; et al. (Environmental and molecular mutagenesis, 2011)
N‐Ethyl‐N‐nitrosourea (ENU) was evaluated as part of the Stage III trial for the rat Pig‐a gene mutation assay. Groups of six‐ to eight‐week‐old male Sprague Dawley (SD) or Fischer 344 (F344) rats were given 28 daily doses of the phosphate buffered saline vehicle, or 2.5, 5, or 10 mg/kg ENU, and evaluated for a variety of genotoxicity endpoints in peripheral blood, spleen, liver, and colon. Blood was sampled predose (Day‐1) and at various time points up to Day 57. Pig‐a mutant frequencies were determined in total red blood cells (RBCs) and reticulocytes (RETs) as RBCCD59− and RETCD59− frequencies. Consistent with the results from a reference laboratory, RBCCD59− and RETCD59− frequencies increased in a dose‐ and time‐dependent manner, producing significant increases at all doses by Day 15, with similar frequencies seen in both rat strains. ENU also induced small but significant increases in % micronucleated RETs on Days 4 and 29. No significant increases in micronuclei were seen in the liver or colon of the ENU‐treated SD rats. Hprt and Pig‐a lymphocyte mutation assays conducted on splenocytes from Day 56 F344 rats detected two‐ to fourfold stronger responses for Hprt than Pig‐a mutations. Results from the in vivo Comet assay in SD rats at Day 29 showed generally weak increases in DNA damage in all tissues evaluated. The results with ENU indicate that the Pig‐a RET and RBC assays are reproducible, transferable, and complement other genotoxicity endpoints that could potentially be integrated into 28‐day repeat‐dose rat studies. © Environ. Mol. Mutagen. 2011. Published 2011 Wiley‐Liss, Inc.